Transforming Dengue Prevention: Community Knowledge and Health Promotion as Keys to Reducing Mortality in Surakarta, Central Java, Indonesia - Akbarudin Arif; Kurnia Atika Suri; Sapja Anantanyu; Agus Kristiyanto; Haryani Saptaningtyas (Journal of Health Promotion and Behavior, 2026)
Background: Dengue Haemorrhagic Fever (DHF) remains a major public health threat in tropical regions like Surakarta, Indonesia. While conventional mosquito control methods such as fogging are widely implemented, their long-term effectiveness is limited. This study investigates how gaps in community knowledge regarding dengue symptoms and warning signs contribute to treatment delays and increased mortality rates.Subjects and Method: The study employed a quantitative-method approach focusing on the year 2024. Due to fieldwork challenges, a total sampling of 11 families who lost members to DHF was conducted using proxies, including relatives, neighborhood heads, and health cadres. Data were collected through semi-structured interviews and analyzed using SPSS for descriptive and inferential statistics, including multiple linear regression and ANOVA analysis.Results: DHF fatalities in Surakarta rose by over 150%, from 4 deaths in 2023 to 11 in 2024, with the 5–14 age group being most vulnerable. Statistical analysis revealed that all 11 families lacked sufficient knowledge of dengue symptoms. While most variables were not statistically significant, family recognition of experienced symptoms was a critical factor in identifying the disease. The high R-square value (91.4%) indicates that knowledge gaps and information access strongly influence DHF awareness.Conclusion: The primary driver of DHF mortality in Surakarta is a critical lack of knowledge among families, leading to fatal delays in seeking medical care. Traditional reactive strategies like fogging are insufficient. Reducing mortality requires a paradigm shift toward inclusive, knowledge-based community empowerment and early warning health education.